PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN PENGGUNA HANDPHONE MEREK SAMSUNG PADA MASYARAKAT MENGANTI 2018 - Khakim, M. Azizul (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2022)
This study aims to analyze the effect of product quality and price on customer loyalty of Samsung brand mobile phone users in the Menganti community in 2018. This type of research is qualitative. Sources of data in the form of secondary data taken from the results of interviews and analyze the character and interests of the community. The research method used is descriptive qualitative. This method is used to analyze the results of respondents' answers to the questionnaire given. Then the data is processed using SPPS 27 software. Brand Value (BV) of personal products in the category of Samsung brand mobile phones from 2013 to 2016. From the table, it can be seen that Samsung brand mobile phones for a period of 3 years occupy the first position as market leader. However, it is also seen from the BV score that it also tends to relatively decrease from year to year. Keyword: Brand Value, Customer Loyalty, Product Quality, Product Price